Enemy within : German minorities as a weapon of German policy - Borsky, G.; Krek, Miho; Màtrai, András; Niculescu, B.M.; Pragier, Adam (London: Hutchinson & Co., 1942)
"G. Borsky, András Màtrai, Professor A. Pragier, B.M. Niculescu, Dr. Miho Krek Bibliotheek Camille Huysmans"